Missed Nursing Care and Unit-Level Nurse Workload in the Acute and Post-Acute Settings. Issue 1 (January 2016) - Orique, Sabrina B.; Patty, Christopher M.; Woods, Ellen
Abstract : This study replicates previous research on the nature and causes of missed nursing care and adds an explanatory variable: unit-level nurse workload (patient turnover percentage). The study was conducted in California, which legally mandates nurse staffing ratios. Findings demonstrated no significant relationship between patient turnover and missed nursing care. Abstract : Supplemental Digital Content is Available in the Text.